Profile of Total Leukocytes and Differential Leukocytes in Broilers Using Herbal Feed Additives - Mardhotillah, Achmad Bagus Adhiluhung; Hidayah, Nur; Ali, Usman; Sjofjan, Osfar; Djunaidi, Irfan (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
ABSTRACTThis study aims to determine the effect of herbal plant-based feed additives, namely Aloe vera and turmeric flour on the appearance of total leukocytes and leukocyte differential in broilers. The material used for this research is 64 Day old Chick (DOC). The method used a Completely Randomized Design (CRD) with 4 treatments and 4 replicates which contained 4 heads. Total leukocytes profile and leukocyte differential including eosinophils, basophils, heterophils, lymphocytes, and monocytes were observed in this study. The results showed that the combination of Aloe vera and turmeric flour had a significant effect (p<0.01) on total leukocytes (10.73±0.43). Another result in this study was that the combination of herbal feed additives had no effect (p>0.05) on eosinophils (0.27±0.25) and basophils (0.03±0.05), however heterophile (3.42±0.45), lymphocytes (6.48±0.16), and monocytes (0.54±0.16) showed a significant effect (p<0.05). The conclusion is that the addition of herbal feed additives from Aloe vera flour, turmeric flour, and their combination can improve and enhance immune conditions in terms of the total leukocytes and leukocyte differential profiles in broilers.Keywords: Aloe vera flour, turmeric flour, leukocyte profile, antimicrobial